Optimasi UV-Photolithography Aligner dan Photomask Menggunakan Produk Komersial untuk Microfabrication - Delffika Canra; Dedi Suwandi (Jurnal Teknologi Terapan, 2016)
The high price of a UV-photolithography aligner on the market is the reason for designing and characterize low cost UV-photolithography aligner. Photolithography process is simple but it needs patience, enable to modify photolithography aligner by using commercial components and certainly low price. The objective of this study is analyzing the ability of a commercial product in UV-photolithography process, search optimum exposure time and resolution. The method of photolithography process to be used is the method of contact alignment. Commercial UV lamps and cheap photomask are main component in this study. With a light intensity of 0.2 mW/cm2 require the exposure time at least 50 seconds. The smallest achievable resolution depends on the resolution photomask. The Results of smallest resolution is 165 m with a percentage error 10% of the original design.